Upaya Pemerintah Daerah dalam Pengendalian Produksi Minuman Beralkohol Tradisional - Luffita Alfianti (Universitas Airlangga, 2018)
Traditional alcoholic beverage, traditionally produced with hereditay recipe which is drunk to celebrate religious or tradition event. Government have not regulated a distinctive act to control production, so it needs to be analyzed the writer compose a thesis with systematical interpretation and extention to Regional Governance Act Number 23/2014, Ministry of Industry Regulation number 63/M-IND/PER/7/2014 in Restraining and Controlling The Industry and Quality of Beverage, Ministry of Trade Ragulation No. 20/M-Dag/Per/4/2014 in Restraining and Controlling of Supply, Distribution and Sale of Alcoholic Beverage, Head of Drug and Food Board Regulation Number HK.03.1.23.04.12.2205 in Guidelines On The Provision of Certificates of Food Production of Household Industries. Furthermore, writer also examine about Regional Government’s liability in controlling the production of traditional alcoholic beverage. Based on systematical interpretation and extention to regulation above, Regional/Local government has authorization in issuing a permit of traditional alcoholic beverage. However, there is no regulation that organizes the authority of local government to give license to the production of it. In contrast, local government has authority to control the distribution of traditional alcoholic beverage with implements the regulation inforcement to business activities that violate the license to trade by selling traditional alcoholic beverages.